2002
DOI: 10.1080/07481180290086754
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Thanatology in a Foreign Country: Implications for Death Educators

Abstract: Although an increasing number of death educators will have the opportunity to teach abroad, many may not be fully aware of the issues that arise in intercultural instruction and are not prepared to handle the pedagogical challenges associated with teaching thanatology in a foreign country. On the basis of experience of teaching in China, the author describes the challenges of intercultural teaching, strategies for adapting instruction to address the pedagogical obstacles, and the ways an international teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…Although many of the references in this paper noted remarkable differences between Western and Eastern students, Sarkodie‐Mensah (1991), Wu (2002), and Shatz (2002) especially noted that great hierarchical differences exist between teachers and students in different cultures. These authors and the participants in this study are all in agreement with Gao (2002), who observed that in China, for example, notions of attitude promotion and conduct guidance prevail.…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…Although many of the references in this paper noted remarkable differences between Western and Eastern students, Sarkodie‐Mensah (1991), Wu (2002), and Shatz (2002) especially noted that great hierarchical differences exist between teachers and students in different cultures. These authors and the participants in this study are all in agreement with Gao (2002), who observed that in China, for example, notions of attitude promotion and conduct guidance prevail.…”
Section: Resultsmentioning
confidence: 65%
“…Shatz (2002) recounted his experiences as a foreign college instructor in Hong Kong and made similar observations as Kuhn's. He also raised the issue of communication and was in total agreement with Fortuijn (2002), who emphasized that communication barriers can be a major issue in international or cross‐cultural education.…”
Section: Teaching As Cross‐cultural Experiencementioning
confidence: 68%
See 3 more Smart Citations